The Role of Mekar Sewu BUMDes as a Regulator in the Economy of the Kendalsewu Village Community, Tarik District, Sidoarjo Regency - Lestari, Wahyu Indah; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2019)
BUMDes is a village business institution that is managed by the community and village government in an effort to strengthen the village economy and is formed based on the needs and potential of the village. BUMDes savings and loans is a type of business that is engaged in the association and distribution of funds to the public. This study aims to describe and analyze the role of BUMDes as a regulator in the community's economy and to describe and analyze the constraints in the role of BUMDes for Savings and Loans Mekar Sewu in Kendalsewu Village, Tarik District, Sidoarjo Regency. This type of qualitative descriptive research with the technique of determining the informant using purposive sampling. Research informants were the Kendalsewu Village, the Kendalsewu Village secretary, the chief executive of the Mekar Sewu Savings and Loans BUMDes, the Mekar Sewu Savings and Loans BUMDes treasurer, and the borrowing community of the Mekar Sewu BUMDes Savings and Loans. The location of this research is in Kendalsewu Village, Tarik District, Sidoarjo Regency. Data collection techniques are observation, interviews, and documentation. Data analysis techniques from Miles and Huberman (2011: 247) are data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate the role of BUMDes as a regulator in the community's economy at the Mekar Sewu Savings and Loans BUMDes in Kendalsewu Village, Tarik District, Sidoarjo Regency. achieved. The role of BUMDes in Kendalsewu Village is as a regulator of the running of the Mekar Sewu Savings and Loans BUMDes program. BUMDes Mekar Sewu also has stipulation regulations. The obstacle in the role of the Mekar Sewu Savings and Loans BUMDes is the change in the targets that have been set and the lack of awareness of the borrowing community of the Mekar Sewu BUMDes Savings and Loans in timely payments